2013
DOI: 10.7733/jkrws.2013.11.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Zr Recovery from 50 g Scale Zircaloy-4 Cladding Hulls using a Chlorination Method

Abstract: The recovery of Zr from Zircaloy-4 (Zry-4) cladding hulls using a chlorination method was demonstrated for complete conversion of Zr into ZrCl 4 . A chlorination reaction was performed by reacting Zry-4 hulls for 8 h under a 70 cc/min Cl 2 + 70 cc/min Ar flow at 380 o C. The initial weight of the reactant (51.7 g) decreased to 0.49 g after 8 h of operation, which is only 0.95wt% of the initial weight. The weight of the total reaction products was 121.7 g with a high Zr purity of 99.80wt%. Fe and Sn were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…In our previous study [13], where an extraction of Zr from oxidized Zry-4 hulls was demonstrated at a 50 g scale, the amount of reaction residue was 0.95wt%, which is identical to the case of the fresh Zry-4 of the present study. Therefore, it is not reasonable to clarify a relationship between the oxidation process and the amount of reaction residue at this stage.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In our previous study [13], where an extraction of Zr from oxidized Zry-4 hulls was demonstrated at a 50 g scale, the amount of reaction residue was 0.95wt%, which is identical to the case of the fresh Zry-4 of the present study. Therefore, it is not reasonable to clarify a relationship between the oxidation process and the amount of reaction residue at this stage.…”
Section: Resultssupporting
confidence: 85%
“…Several reports were published on the treatment of cladding hull waste through the chlorination process [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zirconium tetrachloride is encountered in the nuclear fuel cycle for the recycling of zirconium from zirconium alloy cladding using a chloride volatility process (Bohe et al, 1996;Collins et al, 2012;Jeon et al, 2013). The ZrCl 4 produced from these alloys at temperatures above 573 K contains several impurities that are difficult to separate.…”
Section: Structure Descriptionmentioning
confidence: 99%